Fatal anaphylaxis in systemic mastocytosis. Issue 1 (January 1979) - Dodd, N J; Bond, M G
Abstract : A 42-year-old woman died after an episode of anaphylaxis associated with a raised serum histamine level. A diagnosis of systemic mastocytosis was established, with lymphadenopathy and hepatosplenomegaly, not associated with the usually pre-existing skin lesions of urticaria pigmentosa.